Primeri uporabe IKT pri športnem plezanju - Kodrin, Matej (Šport (Ljubljana), 2021)
Information and communication technology (ICT) can be a useful tool for providing information, improving the quality of the demonstration, or diversifying lessons. In this paper, some possibilities of using ICT in the content of sport climbing are presented. Activities can be useful for sports teachers, sports program providers or sport climbing coaches.
Keywords: informacijsko komunikacijska tehnologija; information and communication technologies; physical education; sport; sport climbing; šport; športna vzgoja; športno plezanje